Perolehan Suara Partai Politik di Kabupaten Langkat Tahun 2009 - IRMAYANI, T. (Politeia: Jurnal Ilmu Politik, 2010)
The General Election in 2009 has been completed in Indonesia, included in Langkat Regency. There is an interesting phenomenon of the conduct of these elections. This study uses political behavioral approach and institusional. This study aimed to look at the votes of political parties in the years 1999-2009. Then, describe the phenomenon of peoples choice in the legislative elections in Langkat. The results show that in election years 1999, 2004 and 2009, always going changes in the direction of votes of voters. If in the year 1999 the Indonesian Democratic Party of Struggle (PDIP) is winning, the most votes in 2004 were replaced by the Golkar Party (Partai Golkar). Next General Election (2009) in the Langkat Regency show the emergence of the Democratic Party (Partai Demokrat) as the party most votes miners. These results indicate that voterâs choices at Langkat Regency are difficult to conjecture. So that it can be said the election results in Langkat follow the election result in national stage.Keywords: General elections, Political parties, Direction of vote.